The financial performance of islamic unit trusts: a Malaysian perspective / Normala Shariff - Shariff, Normala (2002)
Islamic trust funds is a relatively new capital market instrument and provide investors with an alternative form of portfolio investment that is based on Syariah principles. The financial performance of Islamic unit trusts in Malaysia is analyzed over a period of 36 months commencing February 1999 to January 2002. The measurement yardstick for performance employed are the Sharpe (1966), Treynor (1965) and Jensen (1968) Indices. The investment performance of the Islamic trust funds were evaluated as compared to the market index, Kuala Lumpur Stock Exchange Composite Index (KLCI). The study also aims to identify the nature and characteristics of Islamic unit trusts. In addition the return and risk profile of Islamic trust funds is assessed to gain a better insight of the funds performance. The degree of diversification of Islamic unit trust funds as compared to the market portfolio is also examined. Spearman rank correlation is utilized to analyze fund performance ranking and the persistence of ranking of fund temporal performance. A large majority of the Islamic unit trust funds exhibited superior performance outperforming the market over the period under study. Although the risk profile of Islamic trust funds seems stable over time, they have low degree of diversification. It is also observed that the ranking of temporal performance of Islamic unit trust funds is not persistent over time.